Sticking around: short-range activity of Wnt ligands - Boutros, Michael; Niehrs, Christof (Developmental cell, 2016)
Wnt ligands are secreted lipid-modified proteins that are essential for development and homeostasis. Published recently in Nature, Farin et al. (2016) report that Wnt3 acts at a short distance during growth of mouse intestinal organoids, suggesting that Wnt proteins remain membrane-bound to activate signaling at a short range from their source.